Management of phaeochromocytoma and paraganglioma in patients with germline SDHB pathogenic variants: an international expert Consensus statement - Taïeb, David; Nölting, Svenja; Perrier, Nancy D; Fassnacht, Martin; Carrasquillo, Jorge A; Grossman, Ashley B; Clifton-Bligh, Roderick; Wanna, George B; Schwam, Zachary G; Amar, Laurence; Bourdeau, Isabelle; Casey, Ruth T; et al. (Nature reviews. Endocrinology, 2024)
Adult and paediatric patients with pathogenic variants in the gene encoding succinate dehydrogenase (SDH) subunit B (SDHB) often have locally aggressive, recurrent or metastatic phaeochromocytomas and paragangliomas (PPGLs). Furthermore, SDHB PPGLs have the highest rates of disease-specific morbidity and mortality compared with other hereditary PPGLs. PPGLs with SDHB pathogenic variants are often less differentiated and do not produce substantial amounts of catecholamines (in some patients, they produce only dopamine) compared with other hereditary subtypes, which enables these tumours to grow subclinically for a long time. In addition, SDHB pathogenic variants support tumour growth through high levels of the oncometabolite succinate and other mechanisms related to cancer initiation and progression. As a result, pseudohypoxia and upregulation of genes related to the hypoxia signalling pathway occur, promoting the growth, migration, invasiveness and metastasis of cancer cells. These factors, along with a high rate of metastasis, support early surgical intervention and total resection of PPGLs, regardless of the tumour size. The treatment of metastases is challenging and relies on either local or systemic therapies, or sometimes both. This Consensus statement should help guide clinicians in the diagnosis and management of patients with SDHB PPGLs.
Keywords: zárodečné mutace; dospělí; paragangliom; Adrenal Gland Neoplasms; Germ-Line Mutation; Child; lidé; Paraganglioma; Pheochromocytoma; feochromocytom; dítě; Succinate Dehydrogenase; Adult; sukcinátdehydrogenasa; nádory nadledvin; Humans